Optimization of Vitamin A in Red Guinea Corn-Millet Mix - Eyide, O.; Iweriolor, S.; Ossai, B. J.; Akhihiero, E. T.; Olaseinde, A. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
This study focused on the optimization of vitamin A in guinea corn and millet mix. The concentration of vitamin A was investigated under the following conditions: blending time (1.5 - 5 hours), amount of red guinea corn (10 - 50g) and amount of agro residue (50-100 g) using Box-Behnken design. Statistically significant model (p<0.05) was developed to represent the relationship between the response (concentration of vitamin A) and the independent variables. The model showed a significant fit with experimental data with R2 values of 0.94. Analysis of variance (ANOVA) results showed that the concentration of vitamin A was influenced by the blending time, amount of red guinea corn and amount of millet used. Additionally, response surface methodology (RSM) was used to optimize the concentration of vitamin A. The results showed that maximum concentration of 98.76 µg/100g for vitamin A was obtained at the optimum production conditions of blending time of 5hours, 49.79g of red guinea corn and 100g of millet. The blend produced at the optimized conditions satisfied the World Health Organization (WHO), Food and Agricultural Organization (FAO) specification for recommended safe intake for all age groups, pregnant and nursing mothers.